COMPARATIVE STUDY AGAINST OXIDATIVE STRESS AND DNA DAMAGE PROTECTION ACTIVITY OF THE DIFFERENT EXTRACTS OF TUBERS OF ARISAEMA TORTUOSUM (WALL.) SCHOTT. - PRIYANKA CHAKRABORTY; NRIPENDRA NATH BALA; DAS, SUDIPTA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Our main aim is to evaluate the comparative in vitro antioxidant and DNA damage protection activity study with different extracts of tubers of Arisaema tortuosum. Methods: A. tortuosum (Wall.) Schott. (Araceae family) is commonly known as whipcord cobra lily, used in India as traditional medicine. In vitro, antioxidant activity was done by six methods including determination of total phenolic and total flavonoid compounds. The DNA damage was estimated by standard diphenylamine reaction. Results: Methanolic extract of tubers of A. tortuosum has been found rich in phenolic and flavonoid compounds when compared with other extracts. Methanolic extract of rhizomes of A. tortuosum showed potent antioxidant activity at a concentration of 400 μg/mL and potent the DNA damage protecting activity at a concentration of 50 μg/mL. Conclusion: Comparative study against oxidative damage and protection to the DNA damage protection activity of the different extracts of tubers of A. tortuosum (Wall.) Schott. showed that methanolic extract is most potent, though ethyl acetate extract also showed activity.